STUDY OF GROUNDWATER TABLE CHANGES FROM A WELL BASED ON COMBINING ANALYTICAL AND NUMERICAL METHODS FOR TIME-LAPSE MICROGRAVITY MODELING - Dyah Lestari, Mutia
Groundwater pumping from a well leads to a decline in the groundwater table around the well. The time-lapse microgravity method, an innovative gravity measurement technique, is widely applied for monitoring groundwater table. Pumping changes the subsurface mass distribution, resulting in mass anomalies detectable by gravity methods. Previous studies have employed the slab Bouguer approach to estimate gravity anomalies due to groundwater table changes, but this method is less suitable for local analysis near production wells due to the varying decline in groundwater table relative to the well's distance. According to Theis's formula, the groundwater table decline model, calculated for its gravitational field, takes the shape of an inverted cone, known as a drawdown cone. This study aims to calculate gravity anomalies more accurately in line with the conceptual model of groundwater table changes. Gravity anomalies from the drawdown cone are computed using triple integrals in cylindrical coordinates, combining analytical and numerical methods. The combination is necessary because two of the three variables can be resolved analytically, while the remaining variable requires numerical integration due to the complexity of the function. Analytical calculations in this study address the vertical distance (z) and azimuthal angle (????) variables, while the radial distance (r) is resolved through numerical integration using the trapezoidal rule. By refining the trapezoidal discretization near the well, the numerical calculations are expected to have smaller errors. Simulations show that gravity anomalies are very small, typically in the order of tens of microGal. For a silt aquifer and household well pumping, the gravity anomaly at the well is found to be -11.5 microGal, with the detectable anomaly area using a 5-microGal precision instrument limited to approximately 40 meters from the well. Parameters such as discharge rate and duration are positively correlated with gravity anomaly changes, while specific yield and transmissivity are negatively correlated.